Evaluation of Early Postoperative Outcomes of Open and Laparoscopic Emergency Repair for Incarcerated Anterior Abdominal Wall Hernias - Khalid Ibrahim Akhtar, Rajia Nayaar, Aamer Wadud, Arsalan Siraj, Muhammad Farooq, Qurat Ul Ain Fatima (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Incarcerated anterior abdominal wall hernias represent a frequent surgical emergency with potential for serious complications. Surgical repair can be performed using either open or laparoscopic techniques, each with distinct intraoperative and postoperative profiles. Objectives: To evaluate and compare the early postoperative outcomes of open versus laparoscopic emergency repair in patients with incarcerated anterior abdominal wall hernias. Study Design & Setting: This was a prospective comparative study conducted at the Department of Surgery, HITEC Institute of Medical Sciences and HIT Hospital Taxilla over a period of 6 months. Methodology: A total of 120 patients diagnosed with incarcerated anterior abdominal wall hernias were enrolled and divided into two equal groups: 60 underwent open repair, and 60 underwent laparoscopic repair. Data were collected on demographics, operative details, postoperative pain (VAS), complications, hospital stay, and time to return to normal activity. Statistical analysis was performed using SPSS version 25.0 with a p-value < 0.05 considered significant. Results: The mean operative time was significantly longer in the laparoscopic group (76.2 ± 14.1 min) compared to the open group (64.5 ± 12.3 min; p < 0.001). However, laparoscopic repair resulted in significantly shorter hospital stay (3.9 ± 1.2 vs. 5.8 ± 1.4 days) and faster return to activity (7.6 ± 2.9 vs. 11.2 ± 3.5 days; p < 0.001). Surgical site infections were more frequent in the open group (15% vs. 5%; p = 0.04). Postoperative pain scores were significantly lower in the laparoscopic group on both day 1 and day 3. Clinical Implication: Laparoscopic repair offers superior early postoperative outcomes and should be considered where feasible in emergency settings. Conclusion: Laparoscopic emergency repair was associated with better early outcomes than open repair in incarcerated hernia patients. Keywords: Abdominal hernia, emergency surgery, laparoscopic repair, open hernia repair, postoperative outcomes, surgical site infection.